A broadband low-dispersion optical fiber and its preparation method
By forming a dense interlayer ceramic layer and an ultraviolet shielding film in the optical fiber, the limitations and poor photo-resistant aging performance of traditional optical fibers when transmitting wide band wavelengths for long distances are solved, and the wide band and photo-resistant aging performance of optical fibers are realized. Improvement.
Patent Information
- Application Number
- CN202210172314.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-02-24
AI Technical Summary
Traditional low-dispersive optical fibers have limitations when transmitting wide band wavelengths for long distances, and the photo-resistant aging performance of polyethylene sheaths is poor, resulting in short life and high maintenance costs of optical fibers.
Using low-dispersion glass as the core material, a silicon carbon-nitrogen film is formed through chemical vapor deposition of hot wire and microwave discharge, and a boron nitride film is deposited in combination with a direct current electric field-plasma-assisted pulse laser to form a dense interlayer ceramic layer and rotate on the ceramic layer. Carbon coated quantum dot solution, modified to form an ultraviolet shielding film, using 3,6-octyl glycol, tert-butyl acrylate and bis(2,2,6,6-tetramethylpiperidin-4-yl )amine forms a conjugated system to improve the photo-aging performance of optical fibers.
The broadband performance and photoaging performance of optical fibers are improved, which extends the service life of optical fibers and reduces maintenance costs.
Smart Images

Figure BDA0003518791800000081 
Figure BDA0003518791800000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical fibers, in particular to a broadband low-dispersion optical fiber and a preparation method thereof. Background Art
[0002] Optical fiber communication is the technical foundation of the information society. The development of new optical fiber communication technologies is of great significance. In order to meet social needs, low-dispersion optical fibers have gradually come into people's view. Their advantages such as high gain, good noise performance, and high output power are deeply loved by people; however, due to the limited electrical conductivity of metals and the high absorption coefficient of dielectric materials, traditional low-dispersion optical fibers cannot be used for long-distance transmission of wide-band wavelengths, which has certain limitations on the use of optical fibers.
[0003] In order to protect the normal use of optical fiber and avoid damaging the optical fiber core, polyethylene is often used as the sheath material. Polyethylene has the advantages of light weight, high bending strength, and low friction coefficient, but this kind of pipe still has many disadvantages, such as poor light aging resistance. Under long-term ultraviolet irradiation, the polyethylene molecular chain breaks, cross-links, and degrades, and the life is short. Later maintenance is often required, which greatly increases the cost and causes unnecessary waste. At present, in order to improve the light aging performance of polyethylene, filler measures are mainly used, which not only causes the increase of process costs, but also affects the use of optical fiber. Therefore, how to invent a broadband and light aging resistant optical fiber is particularly important. Summary of the invention
[0004] The object of the present invention is to provide a broadband low-dispersion optical fiber and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a broadband low-dispersion optical fiber, characterized in that, from the inside to the outside, it comprises a core, a ceramic layer, and an ultraviolet shielding film; the core is low-dispersion optical glass.
[0006] Furthermore, the ceramic layer is prepared through a first deposition process, a second deposition process, a sintering process and other steps in sequence.
[0007] Furthermore, the first deposition process: utilizes hot wire chemical vapor deposition, and with the help of microwave discharge, quickly deposits a silicon carbon nitride film on the surface of the wire core to obtain a silicon carbon nitride film wire core; the second deposition process: utilizes DC electric field-plasma assisted pulsed laser deposition of a boron nitride film to obtain a boron nitride film wire core.
[0008] Furthermore, the ultraviolet shielding film is prepared by the following method: after the ceramic layer is pretreated, the surface is spin-coated with a carbon quantum dot solution, and the ceramic layer is modified using 3,6-octanediol, tert-butyl acrylate and bis(2,2,6,6-tetramethylpiperidin-4-yl)amine.
[0009] Furthermore, a method for preparing a broadband low-dispersion optical fiber comprises the following preparation steps:
[0010] (1) The first deposition process: polishing the low-dispersion optical glass to obtain a wire core with a diameter of 5 to 15 mm, ultrasonically cleaning it with acetone at 25 to 35 kHz for 18 to 30 minutes, placing it in a microwave discharge system, evacuating it to 0.02 to 0.1 Pa, introducing monosilane, methane, hydrogen and nitrogen at a flow ratio of 1:1:10:12 to 1:1:15:18 until the pressure reaches 20 to 40 MPa, heating it to 400 to 600° C., and depositing it for 22 to 41 minutes to obtain a silicon carbon nitride thin film wire core;
[0011] (2) Second deposition process: Place the silicon carbon nitride film core in a plasma device, evacuate to 20-40 Pa, pre-sputter for 10-13 min in an argon atmosphere, and then place it in a laser device. Connect the laser device to a DC electric field and evacuate to 10 -6 ~10 -4 Pa, in an argon atmosphere, hexagonal boron nitride was used as a target and deposited for 15 to 22 minutes to obtain a boron nitride thin film core;
[0012] (3) Sintering process: Place the boron nitride film core in a container, heat it to 400-650°C at 10-20°C / min under a nitrogen atmosphere and a pressure of 10-50 MPa, keep it warm for 25-40 minutes, then heat it to 800-1000°C at 1-10°C / min, and then draw it to obtain a core containing a ceramic layer;
[0013] (4) Modification treatment: After pretreatment, the ceramic layer core is spin-coated with a carbon quantum dot solution at 2000-2500 rpm, wherein the mass ratio of carbon quantum dots to toluene in the carbon quantum dot solution is 1:8-1:12. After spin coating for 40-60 seconds, the core is dried at 70-80°C for 1-2 hours, and then immersed in anhydrous ethanol with a mass of 10-15 times that of the ceramic layer core. 3,6-octanediol with a mass of 0.1-0.3 times that of the ceramic layer core is added, and ultrasonically mixed at 30-40 kHz for 10-20 minutes. The core is then placed in a para-polyphenylene lined hydrothermal reactor, heated to 170-180°C, kept warm for 1-2 hours, and cooled to room temperature to obtain a modified optical fiber.
[0014] (5) Secondary modification treatment: The modified optical fiber is placed in a container, and 0.8 to 1.2 times the mass of the modified optical fiber is added with tert-butyl acrylate and 0.001 to 0.006 times the mass of the modified optical fiber is added with tetraisopropyl titanate. Under nitrogen protection, the temperature is raised to 170 to 180°C, and the reaction is carried out for 8 to 10 hours. The fiber is then washed with deionized water for 3 to 6 times. Then, 0.6 to 1.1 times the mass of the modified optical fiber is added with methanol and 1.3 to 1.7 times the mass of the modified optical fiber is added with bis(2,2,6,6-tetramethylpiperidin-4-yl)amine. After stirring evenly, the temperature is raised to 40 to 50°C, and the reaction is carried out for 10 to 12 hours. The fiber is then distilled at 0.1 to 0.3 MPa and 50 to 60°C for 1 to 3 hours. The fiber is cooled to room temperature and dried at 70 to 80°C for 2 to 4 hours to obtain a broadband low-dispersion optical fiber.
[0015] Furthermore, the frequency of the microwave discharge system in step (1) is 2400-2500 MHz, and the power is 100-200 W.
[0016] Furthermore, the plasma sputtering power in step (2) is 100-150W.
[0017] Furthermore, in the laser device of step (2), the distance between the target and the substrate is 5 to 10 cm, and the laser density is 12 to 25 J / cm 2 , the laser wavelength is 532nm, and the DC electric field voltage is 200~400V.
[0018] Furthermore, the wire drawing rate in step (3) is 1 to 4 mm / min; and the diameter of the wire core containing the ceramic layer is 115 to 125 μm.
[0019] Furthermore, the pretreatment in step (4) is as follows: the ceramic layer-containing wire core is cleaned with detergent and cotton wool for 3 to 6 times, and then ultrasonically treated with deionized water, acetone, isopropanol and anhydrous ethanol at 25 to 30 kHz for 7 to 14 minutes, and then vacuum dried at 60 to 80°C and 0.01 to 0.03 MPa for 30 to 45 minutes, and then placed in a container, and ozone is introduced at a rate of 30 to 40 mL / min. After the ozone is introduced for 20 to 30 minutes, the wire core containing the ceramic layer is irradiated with an ultraviolet lamp with a power of 5 to 10 W and a wavelength of 253.7 nm at a position 10 to 20 mm above the ceramic layer-containing wire core for 15 to 20 minutes.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The present invention prepares the optical fiber through the steps of a first deposition process, a second deposition process, a spark plasma sintering process, a modification process and the like in sequence to achieve the functions of light aging resistance and broadband.
[0022] First, the present invention uses low-dispersion glass as the core material, performs the first deposition process, uses hot wire chemical vapor deposition, and generates a non-magnetized highly activated nitrogen reaction with the help of microwave discharge, and quickly deposits a silicon carbon nitrogen film on the surface of the low-dispersion glass; then performs the second deposition process, uses a direct current electric field-plasma assisted pulse laser to deposit a boron nitride film; under the action of the electric field, a large number of charged particles are generated on the surface of the boron nitride, and since the plasma provides an active gas environment, the charged particles react in the active environment, so that the surface has abundant active groups and is easily deposited on the silicon The surface of the carbon nitride film. In addition, the laser gives the charged particles a higher energy, which produces a highly efficient bombardment on the surface of the silicon carbon nitride film. The heat generated greatly promotes the diffusion and penetration of boron nitride on the surface of the silicon carbon nitride film. Finally, a sintering process is performed to melt and bond the boron nitride and silicon carbon nitride to form a densified sandwich ceramic layer. The dielectric constant and dielectric loss of the silicon carbon nitride film and the boron nitride film are low, and they work together to broaden the frequency band of the optical fiber. At the same time, the sandwich structure of the ceramic layer makes the reflections generated by the optical fiber offset each other within a certain frequency band, thereby improving the broadband performance of the optical fiber.
[0023] Secondly, after the ceramic layer is pretreated, the surface is spin-coated with a carbon quantum dot solution to preliminarily form a UV shielding film, which is then modified by reacting the hydroxyl groups of 3,6-octanediol with the oxygen-containing groups on the surface of the carbon quantum dots to graft them onto the surface of the carbon quantum dots. The remaining hydroxyl groups of 3,6-octanediol react with the ester groups of tert-butyl acrylate, and then the double bonds of tert-butyl acrylate react with the imino groups of bis(2,2,6,6-tetramethylpiperidin-4-yl)amine to form a light-stable film on the carbon quantum dot film, further reducing the absorption of ultraviolet rays by the optical fiber, effectively delaying the light aging of the optical fiber, and extending its service life. In addition, the larger conjugated system formed by 3,6-octanediol, tert-butyl acrylate and bis(2,2,6,6-tetramethylpiperidin-4-yl)amine promotes the regeneration of the UV shielding film on the surface of the optical fiber, stably exists, and effectively improves the light aging resistance of the optical fiber. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe the method in detail. The test methods of various indicators of the optical fiber prepared in the following examples are as follows:
[0026] Broadband: Take optical fibers of the same length to test the broadband effect. Use an optical power meter to measure the optical power at the end and initial end of the optical fiber at a frequency of 0.2 to 2.0 GHz, calculate the absorption loss value, and take the average value; absorption loss value = initial end optical power - end optical power.
[0027] Light aging resistance: Take optical fibers of the same length for light aging resistance test. Place the optical fibers 3 cm away from the UV lamp and expose them to light aging at room temperature for 20 hours. Then use a spectrum loss tester to measure and calculate the loss change rate; loss change rate = (loss after aging - loss before aging) / loss before aging × 100%.
[0028] Example 1
[0029] A method for preparing a broadband low-dispersion optical fiber, the method comprising the following preparation steps:
[0030] (1) The first deposition process: low-dispersion optical glass was polished to obtain a wire core with a diameter of 5 mm. After ultrasonic cleaning with acetone at 25 kHz for 30 min, it was placed in a microwave discharge system with a frequency of 2400 MHz and a power of 100 W, evacuated to 0.02 Pa, and monosilane, methane, hydrogen and nitrogen were introduced at a flow ratio of 1:1:10:12 until the pressure reached 20 MPa. The wire core was heated to 400°C and deposited for 41 min to obtain a silicon carbon nitride thin film wire core.
[0031] (2) Second deposition process: Place the silicon carbon nitride film core in a plasma device with a power of 100 W, evacuate to 20 Pa, pre-sputter for 10 min in an argon atmosphere, and then place it in a laser device connected to a 200 V DC electric field and evacuate to 10 -6 Pa, in argon atmosphere, hexagonal boron nitride was used as the target, the distance between the target and the substrate was 5 cm, and the laser density was 12 J / cm 2 , the laser wavelength is 532nm, and the boron nitride thin film core is obtained by deposition for 22min;
[0032] (3) Sintering process: Place the boron nitride film core in a container, heat it to 400°C at 10°C / min under a nitrogen atmosphere and a pressure of 10 MPa, keep it warm for 40 minutes, then heat it to 800°C at 1°C / min, and then draw it at 1 mm / min to obtain a ceramic layer core with a diameter of 115 μm;
[0033] (4) Modification treatment: The ceramic layer wire core was cleaned with detergent and cotton wool for three times, and then ultrasonically treated with deionized water, acetone, isopropanol and anhydrous ethanol at 25kHz for 14 minutes, and then vacuum dried at 60°C and 0.01MPa for 30 minutes. The wire core was placed in a container and ozone was introduced at 30mL / min. After 30 minutes, an ultraviolet lamp with a power of 5W and a wavelength of 253.7nm was used to irradiate the wire core 10mm above the ceramic layer. After treatment for 20 minutes, The carbon quantum dot solution was spin-coated at 2000 rpm, the mass ratio of carbon quantum dots to toluene in the carbon quantum dot solution was 1:8, after spin-coating for 60 seconds, it was dried at 70°C for 2 hours, and then immersed in anhydrous ethanol with a mass of 10 times that of the ceramic layer core, and 3,6-octanediol with a mass of 0.1 times that of the ceramic layer core was added, and ultrasonically mixed at 30kHz for 20 minutes, and then placed in a para-polyphenylene lined hydrothermal reactor, heated to 170°C, kept warm for 2 hours, and then cooled to room temperature to obtain a modified optical fiber;
[0034] (5) Secondary modification treatment: The modified optical fiber is placed in a container, and 0.8 times the mass of the modified optical fiber tert-butyl acrylate and 0.001 times the mass of the modified optical fiber are added. Under nitrogen protection, the temperature is raised to 170°C, and after reacting for 10 hours, it is washed with deionized water for 3 times; then 0.6 times the mass of the modified optical fiber methanol and 1.3 times the mass of the modified optical fiber bis(2,2,6,6-tetramethylpiperidin-4-yl)amine are added, and after stirring evenly, the temperature is raised to 40°C, and the reaction is carried out for 12 hours. Then, it is distilled at 0.1 MPa and 50°C for 3 hours, cooled to room temperature, and dried at 70°C for 4 hours to obtain a broadband and low-dispersion optical fiber.
[0035] Example 2
[0036] A method for preparing a broadband low-dispersion optical fiber, the method comprising the following preparation steps:
[0037] (1) The first deposition process: low-dispersion optical glass was polished to obtain a wire core with a diameter of 15 mm. After ultrasonic cleaning with acetone at 35 kHz for 18 min, it was placed in a microwave discharge system with a frequency of 2500 MHz and a power of 200 W, evacuated to 0.1 Pa, and monosilane, methane, hydrogen and nitrogen were introduced at a flow ratio of 1:1:15:18 until the pressure reached 40 MPa. The wire core was heated to 600°C and deposited for 22 min to obtain a silicon carbon nitride thin film wire core.
[0038] (2) Second deposition process: The silicon carbon nitride film core is placed in a plasma device with a power of 150 W, evacuated to 40 Pa, pre-sputtered for 13 min in an argon atmosphere, and then placed in a laser device connected to a 400 V DC electric field and evacuated to 10 -4Pa, in argon atmosphere, hexagonal boron nitride was used as the target, the distance between the target and the substrate was 10 cm, and the laser density was 25 J / cm 2 , the laser wavelength is 532nm, and the boron nitride thin film core is obtained by deposition for 15min;
[0039] (3) Sintering process: Place the boron nitride film core in a container, heat it to 650°C at 20°C / min under a nitrogen atmosphere and a pressure of 50 MPa, keep it warm for 25 min, then heat it to 1000°C at 10°C / min, and then draw it at 4 mm / min to obtain a ceramic layer core with a diameter of 125 μm;
[0040] (4) Modification treatment: The ceramic layer wire core was cleaned with detergent and cotton wool for 6 times, and then ultrasonicated with deionized water, acetone, isopropanol and anhydrous ethanol at 30kHz for 7 minutes, and then vacuum dried at 80°C and 0.03MPa for 45 minutes. The wire core was placed in a container and ozone was introduced at 40mL / min for 20 minutes. After that, an ultraviolet lamp with a power of 10W and a wavelength of 253.7nm was used to irradiate the wire core 20mm above the ceramic layer wire core. After treatment for 15 minutes, The carbon quantum dot solution was spin-coated at 2500 rpm, the mass ratio of carbon quantum dots to toluene in the carbon quantum dot solution was 1:12, after spin-coating for 40 seconds, it was dried at 80°C for 1 hour, and then immersed in anhydrous ethanol with a mass of 15 times that of the core of the ceramic layer, and 3,6-octanediol with a mass of 0.3 times that of the core of the ceramic layer was added, and ultrasonically mixed at 40 kHz for 10 minutes, and then placed in a para-polyphenylene lined hydrothermal reactor, heated to 180°C, kept warm for 1 hour, and cooled to room temperature to obtain a modified optical fiber;
[0041] (5) Secondary modification treatment: The modified optical fiber was placed in a container, and 1.2 times the mass of the modified optical fiber was added with tert-butyl acrylate and 0.006 times the mass of the modified optical fiber was added with tetraisopropyl titanate. Under nitrogen protection, the temperature was raised to 180°C, and the reaction was carried out for 8 hours. The fiber was then washed with deionized water for 6 times. Then, 1.1 times the mass of the modified optical fiber was added with methanol and 1.7 times the mass of the modified optical fiber was bis(2,2,6,6-tetramethylpiperidin-4-yl)amine. After stirring evenly, the temperature was raised to 50°C, and the reaction was carried out for 10 hours. The fiber was then distilled at 0.3 MPa and 60°C for 1 hour. The fiber was cooled to room temperature and dried at 80°C for 2 hours to obtain a broadband and low-dispersion optical fiber.
[0042] Example 3
[0043] A method for preparing a broadband low-dispersion optical fiber, the method comprising the following preparation steps:
[0044] (1) The first deposition process: low-dispersion optical glass was polished to obtain a wire core with a diameter of 10 mm. After ultrasonic cleaning with acetone at 30 kHz for 24 min, it was placed in a microwave discharge system with a frequency of 2450 MHz and a power of 150 W, evacuated to 0.07 Pa, and monosilane, methane, hydrogen and nitrogen were introduced at a flow ratio of 1:1:13:16 until the pressure reached 30 MPa. The wire core was heated to 540°C and deposited for 31 min to obtain a silicon carbon nitride thin film wire core.
[0045] (2) Second deposition process: The silicon carbon nitride film core is placed in a plasma device with a power of 140 W, evacuated to 30 Pa, pre-sputtered for 12 min in an argon atmosphere, and then placed in a laser device connected to a 300 V DC electric field and evacuated to 10 -5 Pa, in argon atmosphere, hexagonal boron nitride was used as the target, the distance between the target and the substrate was 7 cm, and the laser density was 20 J / cm 2 , the laser wavelength is 532nm, and the boron nitride thin film core is obtained by deposition for 17min;
[0046] (3) Sintering process: Place the boron nitride film core in a container, heat it to 580°C at 14°C / min under a nitrogen atmosphere and a pressure of 30 MPa, keep it warm for 33 min, then heat it to 900°C at 4°C / min, and then draw it at 2 mm / min to obtain a ceramic layer core with a diameter of 120 μm;
[0047] (4) Modification treatment: The ceramic layer wire core was cleaned with detergent and cotton wool for 5 times, and then ultrasonicated with deionized water, acetone, isopropanol and anhydrous ethanol at 28kHz for 12min, and then vacuum dried at 72℃ and 0.02MPa for 39min. The wire core was placed in a container and ozone was introduced at 33mL / min for 27min. Then, an ultraviolet lamp with a power of 8W and a wavelength of 253.7nm was used to irradiate the wire core 15mm above the ceramic layer wire core. After treatment for 17min, the wire core was irradiated with an ultraviolet lamp with a power of 8W and a wavelength of 23 00rmp / min spin coating of a carbon quantum dot solution, wherein the mass ratio of carbon quantum dots to toluene in the carbon quantum dot solution is 1:10, after spin coating for 53s, the solution is dried at 77°C for 1.5h, and then immersed in anhydrous ethanol with a mass of 12 times that of the core of the ceramic layer, and 3,6-octanediol with a mass of 0.24 times that of the core of the ceramic layer is added, and ultrasonically mixed at 35kHz for 14min, and then placed in a para-polyphenylene lined hydrothermal reactor, heated to 176°C, kept warm for 1.5h, and then cooled to room temperature to obtain a modified optical fiber;
[0048] (5) Secondary modification treatment: The modified optical fiber is placed in a container, and 1.07 times the mass of the modified optical fiber tert-butyl acrylate and 0.004 times the mass of the modified optical fiber are added. Under nitrogen protection, the temperature is raised to 176°C, and the reaction is carried out for 8 to 10 hours. The fiber is then washed with deionized water for 4 times. Then, 0.98 times the mass of the modified optical fiber methanol and 1.56 times the mass of the modified optical fiber bis(2,2,6,6-tetramethylpiperidin-4-yl)amine are added. After stirring evenly, the temperature is raised to 46°C, and the reaction is carried out for 11 hours. The fiber is then distilled at 0.2 MPa and 55°C for 2 hours, cooled to room temperature, and dried at 74°C for 3 hours to obtain a broadband and low-dispersion optical fiber.
[0049] Comparative Example 1
[0050] The difference between Comparative Example 1 and Example 3 is only the difference in step (1), and step (1) is changed to: polish the low-dispersion optical glass to obtain a wire core with a diameter of 10 mm, ultrasonically clean it with acetone at 30 kHz for 24 minutes, place it in a container, evacuate it to 0.07 Pa, introduce monosilane, methane, hydrogen and nitrogen at a flow ratio of 1:1:13:16 until the pressure reaches 30 MPa, heat it to 540°C, and deposit it for 31 minutes to obtain a silicon carbon nitride thin film wire core. The remaining preparation steps are the same as those in Example 3
[0051] Comparative Example 2
[0052] The difference between Comparative Example 2 and Example 3 is only the difference in step (2), which is changed to: placing the silicon carbon nitride film core in a laser device, connecting the laser device to a 300V DC electric field, and evacuating to 10 -5 Pa, in argon atmosphere, hexagonal boron nitride was used as the target, the distance between the target and the substrate was 7 cm, and the laser density was 20 J / cm 2 The laser wavelength is 532 nm, and the boron nitride thin film core is obtained by deposition for 17 minutes. The remaining preparation steps are the same as those in Example 3.
[0053] Comparative Example 3
[0054] The difference between Comparative Example 3 and Example 3 is only the difference in step (2), which is changed to: placing the silicon carbon nitride film core in a plasma device with a power of 140 W, evacuating to 30 Pa, and pre-sputtering for 12 minutes in an argon atmosphere, and then placing it in a laser device and evacuating to 10 -5 Pa, in argon atmosphere, hexagonal boron nitride was used as the target, the distance between the target and the substrate was 7 cm, and the laser density was 20 J / cm 2 The laser wavelength is 532 nm, and the boron nitride thin film core is obtained by deposition for 17 minutes. The remaining preparation steps are the same as those in Example 3.
[0055] Comparative Example 4
[0056] The difference between Comparative Example 4 and Example 3 is that the step (3) is omitted, and the remaining preparation steps are the same as those of Example 3.
[0057] Comparative Example 5
[0058] The difference between Comparative Example 5 and Example 3 is only the difference in step (4), and step (4) is changed to: soak the ceramic layer core in anhydrous ethanol 12 times the mass of the ceramic layer core, add 3,6-octanediol 0.24 times the mass of the ceramic layer core, mix ultrasonically at 35kHz for 14 minutes, then place in a para-polyphenylene lined hydrothermal reactor, heat to 176°C, keep warm for 1.5 hours, and cool to room temperature to obtain a modified optical fiber. The remaining preparation steps are the same as those in Example 3.
[0059] Comparative Example 6
[0060] The difference between Comparative Example 6 and Example 3 is only that step (4) is different. Step (4) is changed to: the ceramic layer core is cleaned with detergent and cotton wool for 5 times, and then ultrasonically treated with deionized water, acetone, isopropanol and anhydrous ethanol at 28kHz for 12 minutes, and then vacuum dried at 72°C and 0.02MPa for 39 minutes, placed in a container, and ozone is introduced at 33mL / min. After 27 minutes, it is irradiated with an ultraviolet lamp with a power of 8W and a wavelength of 253.7nm at a position 15mm above the ceramic layer core. After treatment for 17 minutes, a carbon quantum dot solution is spin-coated at 2300rmp / min. The mass ratio of carbon quantum dots to toluene in the carbon quantum dot solution is 1:10. After spin coating for 53 seconds, it is dried at 77°C for 1.5 hours to obtain a modified optical fiber.
[0061] Comparative Example 7
[0062] The difference between Comparative Example 7 and Example 3 is only the difference in step (5), and step (5) is changed to: place the modified optical fiber in a container, add methanol 0.98 times the mass of the modified optical fiber and bis(2,2,6,6-tetramethylpiperidin-4-yl)amine 1.56 times the mass of the modified optical fiber, stir evenly, heat to 46°C, react for 11 hours, then distill at 0.2 MPa and 55°C for 2 hours, cool to room temperature, and dry at 74°C for 3 hours to obtain a broadband low-dispersion optical fiber. The remaining preparation steps are the same as those in Example 3.
[0063] Effect example
[0064] Table 1 below shows the performance analysis results of the optical fibers using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0065] Table 1
[0066]
[0067]
[0068] From the comparison of the absorption loss experimental data of the embodiment and the comparative example, it can be found that the first deposition process, the second deposition process, and the sintering process are sequentially performed to form a uniform and dense sandwich ceramic layer on the surface of the low-dispersion glass, the boron nitride film and the silicon carbon nitride film are melt-bonded and tightly cross-linked, and the silicon carbon nitride film and the boron nitride film have low dielectric constants and dielectric losses, and work together to broaden the frequency band of the optical fiber. At the same time, the sandwich structure of the ceramic layer allows the reflections generated by the optical fiber to offset each other within a certain frequency band, thereby improving the broadband performance of the optical fiber. From the embodiment and the comparative example, Comparison of the loss change rate experimental data shows that a carbon quantum dot film is introduced into the optical fiber film to form a UV shielding film, and 3,6-octanediol, tert-butyl acrylate and bis(2,2,6,6-tetramethylpiperidin-4-yl)amine are used to modify it in sequence to form a light-stable film on the basis of the carbon quantum dot film, which further reduces the absorption of ultraviolet rays by the optical fiber, effectively delays the light aging of the optical fiber, extends its service life, and promotes the regeneration of the UV shielding film on the surface of the optical fiber, which exists stably and effectively improves the light aging resistance of the optical fiber.
[0069] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A broadband low-dispersion optical fiber, characterized in that: From the inside to the outside, there are a wire core, a ceramic layer, and a UV shielding film; the wire core is low-dispersion optical glass; The method for preparing the broadband low-dispersion optical fiber comprises the following steps: (1) The first deposition process: polish the low-dispersion optical glass to obtain a wire core with a diameter of 5-15 mm, clean it with acetone ultrasonically at 25-35 kHz for 18-30 min, place it in a microwave discharge system, evacuate it to 0.02-0.1 Pa, introduce monosilane, methane, hydrogen and nitrogen at a flow ratio of 1:1:10:12-1:1:15:18 until the pressure reaches 20-40 MPa, heat it to 400-600 °C, and deposit it for 22-41 min to obtain a silicon carbon nitride thin film wire core; (2) Second deposition process: Place the silicon carbon nitride film core in a plasma device, evacuate to 20-40 Pa, pre-sputter at a power of 100-150 W for 10-13 min in an argon atmosphere, and then place it in a laser device. Connect the laser device to a DC electric field and evacuate to 10 -6 ~10 -4 Pa, in an argon atmosphere, hexagonal boron nitride was used as a target and deposited for 15 to 22 minutes to obtain a boron nitride film core; (3) Sintering process: Place the boron nitride film core in a container, heat it to 400~650℃ at 10~20℃ / min under a nitrogen atmosphere and a pressure of 10~50MPa, keep it warm for 25~40min, then heat it to 800~1000℃ at 1~10℃ / min, and then draw it to obtain a core containing a ceramic layer; (4) Modification treatment: After pretreatment, the ceramic layer core is spin-coated with a carbon quantum dot solution at 2000-2500 rpm. The mass ratio of carbon quantum dots to toluene in the carbon quantum dot solution is 1:8-1:
12. After spin coating for 40-60 seconds, the core is dried at 70-80°C for 1-2 hours, and then immersed in anhydrous ethanol with a mass of 10-15 times that of the ceramic layer core. 3,6-octanediol with a mass of 0.1-0.3 times that of the ceramic layer core is added, and ultrasonic mixing is performed at 30-40 kHz for 10-20 minutes. The core is then placed in a para-polyphenylene lined hydrothermal reactor, heated to 170-180°C, and kept warm for 1-2 hours. Cooling to room temperature, a modified optical fiber is obtained; the pretreatment: washing the ceramic layer core with detergent and absorbent cotton for 3 to 6 times, then using deionized water, acetone, isopropanol and anhydrous ethanol in turn for 7 to 14 minutes at 25 to 30kHz ultrasonic, and then vacuum drying at 60 to 80°C and 0.01 to 0.03MPa for 30 to 45 minutes, placing in a container, passing ozone at 30 to 40mL / min, passing for 20 to 30 minutes, and then irradiating with an ultraviolet lamp with a power of 5 to 10W and a wavelength of 253.7nm at 10 to 20mm above the ceramic layer core for 15 to 20 minutes; (5) Secondary modification: Place the modified optical fiber in a container, add 0.8-1.2 times the mass of the modified optical fiber tert-butyl acrylate and 0.001-0.006 times the mass of the modified optical fiber tetraisopropyl titanate, heat to 170-180°C under nitrogen protection, react for 8-10 hours, and then wash with deionized water for 3-6 times; then add 0.6-1.1 times the mass of the modified optical fiber methanol and 1.3-1.7 times the mass of the modified optical fiber bis(2,2,6,6-tetramethylpiperidin-4-yl)amine, stir evenly, heat to 40-50°C, react for 10-12 hours, and then distill at 0.1-0.3 MPa and 50-60°C for 1-3 hours, cool to room temperature, and dry at 70-80°C for 2-4 hours to obtain a broadband low-dispersion optical fiber.
2. A broadband low-dispersion optical fiber according to claim 1, characterized in that: The frequency of the microwave discharge system in step (1) is 2400-2500 MHz, and the power is 100-200 W.
3. The broadband low-dispersion optical fiber according to claim 1, characterized in that: The laser equipment in step (2): the distance between the target and the substrate is 5-10 cm, and the laser density is 12-25 J / cm 2 , the laser wavelength is 532nm, and the DC electric field voltage is 200~400V.
4. The broadband low-dispersion optical fiber according to claim 1, characterized in that: The wire drawing rate in step (3) is 1-4 mm / min; the diameter of the wire core containing the ceramic layer is 115-125 μm.
